SZ_GERICHTE BEK 2020 85 vom 9. Juli 2020 , Geschwindigkeitsüberschreitung (Rechtzeitigkeit der Einsprache) - SZ Gerichte (2020)
Geschwindigkeitsüberschreitung (Rechtzeitigkeit der Einsprache) | übriges Strafrecht